Occupational Safety and Health Management System (OSH-MS) for Sewage Treatment Plants - Malakahmad, Dr, Amirhossein, Dr (2009)
Wastewater treatment plant operators are exposed to a variety of hazardous chemical agents contained within the effluents and the reagents used in the wastewater processing or generated during the wastewaters treatment. These chemical agents may cause acute poisoning, chemical accidents (e.g., skin burns, injury to the eyes, etc.) damage to the respiratory system, allergies, dermatitis and chronic diseases. In addition, operators may be injured by slips, trips and falls on wet floors; falls into treatment ponds, pits, clarifiers or vats or splashes of hazardous liquids; they may also suffer cuts and pricks from sharp tools. Furthermore, they are exposed to hazards related to work in confined spaces. Other common hazards include electric shock, explosions, entanglement in moving machinery, etc. The aim of this study is to identify these hazards at sewage treatments plants particularly in Malaysia. Then, based on likelihood and severity the most risky hazards in the area of study will be assessed. Next, according to produced list of hazard, proper management system via hierarchy of control (Elimination, Substitution, Isolation, Engineering Controls, Administrative Controls, Personal Protective Equipment) will be applied.